Is there a basic framework for training in demography? - Wajnman, Simone; Gonçalves-Rio Neto, Eduardo Luís (Papeles de Población; Vol. 9 Núm. 36 (2003): Papeles de Población, 2021)
This paper reviews our story from the starting point —as a specialization area in demography within the master’s program of economics —to the present—- a nationally top-ranked graduate program (master’s and doctoral) in demography. Our successful experience is largely due to balanced integration of formal and substantive demography. It is due to our 30 years of experience in teaching demography in Cedeplar that we feel comfortable to discuss what we understand to be a basic framework for training in Demography. Thus, we argue that the basic framework for teaching demography is the integration of formal and substantive demography as a backbone, along with innovations that inevitably enhance the trainees’ abilities to face the new challenge and issues in their professional careers.